The Immediate Effects of Deep Pressure on Young People with Autism and Severe Intellectual Difficulties: Demonstrating Individual Differences - Lana Bestbier; Tim I. Williams (Occupational Therapy International)
Background. Deep pressure is widely used by occupational therapists for people with autism spectrum disorders. There is limited research evaluating deep pressure. Objective. To evaluate the immediate effects of deep pressure on young people with autism and severe intellectual disabilities. Methods. Mood and behaviour were rated for 13 pupils with ASD and severe ID before and after deep pressure sessions. Results. Sufficient data was available from 8 participants to be analysed using Tau-U, a nonparametric technique that allows for serial dependence in data. Six showed benefits statistically. Five of these showed benefits across all domains, and one showed benefits on three out of five domains. Relevance to Clinical Practice. Deep pressure appears to be of immediate benefit to this population with autism and severe ID, but the heterogeneity of response suggests that careful monitoring of response should be used and deep pressure discontinued when it is no longer of benefit. Limitations. This is an open label evaluation study using rating scales. Recommendations for Future Research. Future studies of the use of deep pressure should use physiological response measures, in addition to blinded raters for aspects of behaviours such as attitude to learning psychological health not captured physiologically.